A linguagem verbal das TED Talks: uma análise multidimensional - Oliveira, Elaine Cristina de (2021)
The aim of this research was to analyze the verbal language of the popularly called TED Talks videos. For this, we considered the transcripts of 3,411 TED Talks videos in English from 1984 to the end of 2019, collected via TED's official website – forming the corpus called CoTED. The choice of the object of research occurred because, although we find people making references, using, studying, researching, analyzing and collecting the verbal language of the TED Talks, there are still no research on this language from the perspective of the Multidimensional Functional Analysis (MDA) (BIBER, 1988; 2009) – which is based on corpora research using specialized computational tools. The MDA can provide us the underlying parameters of the linguistic characteristics present in a corpus or corpora, that is, it identifies which grammatical-functional characteristics are co-occurring in texts that are part of a particular corpus or corpora. Considering the Additive Functional MDA, the CoTED texts were measured according to the dimensions of the English language found by Biber (1988); and, with the Complete Functional MDA, a complete factor extraction of the CoTED was performed, in order to reveal the dimensions of grammatical-functional variation present in the corpus. Also, through the General Linear Model (GLM) ANOVA procedure, it was possible to verify whether/and how the multidimensional functional variation occurs in terms of the independent variables "presenter" and "event". The results of the Additive and Complete Multidimensional Analysis demonstrated that, for example, the verbal language of the TED Talks is adaptable to both spoken and written language, and that factors external to it exert great influence – bringing the hypothesis that we can consider the TED Talks as a hybrid register. Thus, by understanding the functioning of the language used by the TED Talks, it is expected to contribute to the understanding in detail of the functioning of the verbal language of this influential modality of contemporary communication and contribute directly or indirectly to future studies and possible applications